Oxytocin Pathway Gene (CD38, OXTR) Variants Are Not Related to Psychosocial Characteristics Defined by Strengths and Difficulties Questionnaire in Adolescents: A Field School-Based Study - Tereshchenko, Sergey; Kasparov, Edward; Zobova, Svetlana; Smolnikova, Marina; Evert, Lidia; Semenova, Nadezhda; Zaitseva, Olga; Shubina, Margarita; Gorbacheva, Nina; Lapteva, Ludmila (Frontiers in Psychiatry, 2021)
Background: CD38 is a transmembrane glycoprotein that regulates oxytocin (OT) production and influences social interactions. The oxytocin receptor (OXTR) has been studied intensively regarding its association with human psychosocial functions. Many studies have demonstrated a link between CD38 rs3796863 and OXTR rs53576 polymorphic regions and psychosocial characteristics as well as various psychiatric disorders in adolescents. Some studies, however, have reported null findings. Methods: The Strengths and Difficulties Questionnaire (SDQ) is a brief psychopathologic screening tool recommended for detecting psychosocial problems and psychiatric disorders in adolescents. The current field school-based study, conducted among urban Siberian adolescents (n = 298 aged 12–18), explored the SDQ scales in relation to polymorphisms of the CD38 and the OXTR genes (rs3796863 and rs53576, respectively). Results: None of the studied genotypes were associated with the SDQ results for the complete sample with presumed statistical power as 0.8 to detect a medium-size effect (Cramer's V = 0.3) at α = 0.0083. Post hoc analysis in subgroups showed that OT pathway high activity may cause some negative consequences, such as emotional instability in older (aged 15–18) adolescent boys who are carriers of the rs53576 GG variant. Conclusion: Variations at the CD38 rs3796863 and OXTR rs53576 loci were not associated with psychosocial characteristics of adolescents assessed with the SDQ. In studies with a similar design, we recommend replication with larger samples and greater power to detect small effects, especially in age–sex subgroups of adolescents.